REPRESENTASI ETNIS KETURUNAN ARAB DI INDONESIA DALAM FILM 3 HATI DUA DUNIA SATU CINTA : (Analisis Makna Denotasi dan Konotasi) - Khafid Oktavian; Miftahul Mufid (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Film semiotics is one of the semiotic studies that uses film as its object. This study aims to determine the meaning of denotation and connotation contained in a film through semiotic analysis. This study discusses how the ethnic representation of Indonesian Arab descent in the film 3 Hati Dua Dunia Satu Cinta which aired in July 2010. The theory used is representation theory and uses a qualitative approach with semiotic analysis of Roland Barthes. The unit of analysis focuses on scenes that describe the lives of ethnic Indonesian Arab descendants. Data collection techniques in the form of documentation and literature study. The analysis was carried out by analyzing the data, describing each scene containing ethnic representations of Arab descent by looking for the denotative and connotative meanings contained in the scenes from the film, then carrying out the analysis process using Roland Barthes' semiotic theory. The results of the study show that in the film there are signs that describe the life of ethnic Indonesian Arab descent in the film 3 Hati Dua Dunia Satu Cinta which are represented through Arab attributes, such as the use of a robe and white cap for men, and the use of headscarves for men. woman. And in their cultural system, such as speaking using a mixed language of Arabic and Indonesian, their economic system which is predominantly trading, the matchmaking system and their artistic traditions such as Zapin dance and Gambus music.